Influence of social media information acceptance on university students' shopping intention - SHAHZALAL, MD (Technium Business and Management, 2025)
This study examines how accepting information on social media—and the factors that shape that acceptance—affects students’ intention to shop for sustainable goods. A survey of 160 Bangladeshi university students found clear, consistent patterns. Positive attitudes toward information on social media increased both the perceived usefulness of that information and the willingness to accept it, and also directly raised intention to shop via social platforms. Perceived usefulness further strengthened information acceptance, and acceptance, in turn, increased shopping intention. Attitudes toward information had the strongest effect on perceived usefulness and a sizable direct effect on intention, revealing two pathways: a direct persuasive route and an indirect route through usefulness and acceptance. These results extend established behavioral and information-adoption theories to a developing, collectivist setting. Practically, brands and educators should provide transparent, specific, and verifiable content, and support peer-led communities that help students judge credibility—thereby turning interest in sustainability into confident purchase intentions.